Clinically Important Resistance among Salmonella enterica Serotype Typhi Isolates—United States, 2003–2015. (4th October 2017) - Medalla, Felicita; Watkins, Louise Francois; Chatham-Stephens, Kevin; Reynolds, Jared; Bicknese, Amelia; Friedman, Cindy
Abstract: Background: Salmonella Typhi (Typhi) causes typhoid fever, accounting for an estimated 5, 700 illnesses and 623 hospitalizations per year in the United States. Most infections are acquired during travel to regions outside the United States where typhoid fever is prevalent and antimicrobial resistance is a problem. Fluoroquinolones (e.g., ciprofloxacin) are considered the treatment of choice for susceptible Typhi infections due to their superior ability to concentrate intracellularly and in bile, however, nonsusceptibility has been associated with treatment failure or delayed response. Azithromycin and ceftriaxone are treatment options. We describe antimicrobial susceptibility among Typhi isolates in the United States and the implications for management. Methods: The National Antimicrobial Resistance Monitoring System at CDC conducts susceptibility testing on all Typhi isolates submitted by public health laboratories. We used broth microdilution to determine minimum inhibitory concentrations (MICs) to agents representing 9 antimicrobial classes and categorized isolates according to criteria from the Clinical and Laboratory Standards Institute. We defined ciprofloxacin nonsusceptibility as MIC ≥0.12 μg/mL, ciprofloxacin resistance as MIC ≥1, azithromycin resistance as MIC ≥32, and ceftriaxone resistance as MIC ≥4. Results: From 2003–2015, isolates were tested from 4, 550 patients; 2, 760 (61%) were ciprofloxacin nonsusceptible, 4% were ciprofloxacin resistant. One isolate was azithromycin resistant and none were ceftriaxone resistant. Ciprofloxacin nonsusceptibility increased from 39% in 2003 to 66% in 2015; resistance increased from 0.3% to 8%. Median age of patients was 23 years (range 1–99 years), 53% were male, most were from the Northeast (33%) or the West (29%), and 74% had an isolate from blood. Conclusion: Two thirds of Typhi isolates exhibited ciprofloxacin nonsusceptibility, which has increased over the last decade, and full resistance is increasing. Clinicians should be aware of high rates of fluoroquinolone nonsusceptibility when selecting empiric therapy and should tailor antimicrobial treatment to susceptibility results when feasible. Azithromycin and ceftriaxone remain important treatment options. Disclosures: All authors: No reported disclosures.